Activation of alpha-Fe2O3 for Photoelectrochemical Water Splitting Strongly Enhanced by Low Temperature Annealing in Low Oxygen Containing Ambient - Makimizu, Yoichi; Nguyen, Nhat Truong; Tucek, Jiri; Ahn, Hyo-Jin; Yoo, Jeong Eun; Poornajar, Mahshid; Hwang, Imgon; Kment, Stepan; Schmuki, Patrik (Chemistry - A European Journal, 2020)
Photoelectrochemical (PEC) water splitting is a promising method for the conversion of solar energy into chemical energy stored in the form of hydrogen. Nanostructured hematite (alpha-Fe2O3) is one of the most attractive materials for a highly efficient charge carrier generation and collection due to its large specific surface area and the short minority carrier diffusion length. In the present work, the PEC water splitting performance of nanostructured alpha-Fe2O3 is investigated which was prepared by anodization followed by annealing in a low oxygen ambient (0.03 % O-2 in Ar). It was found that low oxygen annealing can activate a significant PEC response of alpha-Fe2O3 even at a low temperature of 400 degrees C and provide an excellent PEC performance compared with classic air annealing. The photocurrent of the alpha-Fe2O3 annealed in the low oxygen at 1.5 V vs. RHE results as 0.5 mA cm(-2), being 20 times higher than that of annealing in air. The obtained results show that the alpha-Fe2O3 annealed in low oxygen contains beneficial defects and promotes the transport of holes; it can be attributed to the improvement of conductivity due to the introduction of suitable oxygen vacancies in the alpha-Fe2O3. Additionally, we demonstrate the photocurrent of alpha-Fe2O3 annealed in low oxygen ambient can be further enhanced by Zn-Co LDH, which is a co-catalyst of oxygen evolution reaction. This indicates low oxygen annealing generates a promising method to obtain an excellent PEC water splitting performance from alpha-Fe2O3 photoanodes.
CRIS-Team WoS Importer:2020-02-21

Effects of low oxygen annealing on the photoelectrochemical water splitting properties of α-Fe2O3 - Makimizu, Yoichi; Yoo, Jeong Eun; Poornajar, Mahshid; Nguyen, Nhat Truong; Ahn, Hyo-Jin; Hwang, Imgon; Kment, Stepan; Schmuki, Patrik (Journal of Materials Chemistry A, 2020)
Photoelectrochemical (PEC) water splitting is a promising method for converting solar energy into chemical energy stored in the form of hydrogen. Nanostructured hematite (α-Fe2O3) is one of the most attractive materials for highly efficient charge carrier generation and collection, due to its large specific surface area and shortened minority carrier diffusion length required to reach the surface. In the present work, PEC water splitting performance of α-Fe2O3 prepared by anodization of thin iron layers on FTO glass and subsequent annealing in a low O2-Ar atmosphere with only 0.03% O2 was investigated. The key finding is that annealing anodic nanostructures with a low oxygen concentration provides a strongly enhanced PEC performance compared with classical air annealing. The photocurrent of the former at 1.5 V vs. RHE results in 1.1 mA cm-2, being 11 times higher than that of the latter. The enhancement of the PEC performance of α-Fe2O3 annealed in a low oxygen atmosphere can be attributed to the controlled morphology, Sn doping, and introduction of oxygen vacancies, which contribute to the enhancement of the hole flux from the photogenerated site to the reactive surface and additionally lead to an enhanced hole transfer at the interface between α-Fe2O3 and the electrolyte. From the obtained results, it is evident that low oxygen annealing is a surprisingly effective method of defect engineering and optimizing α-Fe2O3 electrodes for a maximized PEC water splitting performance.
CRIS-Team Scopus Importer:2020-02-07

Fe2O3 Blocking Layer Produced by Cyclic Voltammetry Leads to Improved Photoelectrochemical Performance of Hematite Nanorods - Poornajar, Mahshid; Nguyen, Nhat Truong; Ahn, Hyo-Jin; Buechler, Markus; Liu, Ning; Kment, Stepan; Zbořil, Radek; Yoo, Jeong Eun; Schmuki, Patrik (Surfaces, 2019)
Hematite is a low band gap, earth abundant semiconductor and it is considered to be a promising choice for photoelectrochemical water splitting. However, as a bulk material its efficiency is low because of excessive bulk, surface, and interface recombination. In the present work, we propose a strategy to prepare a hematite (alpha -Fe2O3) photoanode consisting of hematite nanorods grown onto an iron oxide blocking layer. This blocking layer is formed from a sputter deposited thin metallic iron film on fluorine doped tin oxide (FTO) by using cyclic voltammetry to fully convert the film into an anodic oxide. In a second step, hematite nanorods (NR) are grown onto the layer using a hydrothermal approach. In this geometry, the hematite sub-layer works as a barrier for electron back diffusion (a blocking layer). This suppresses recombination, and the maximum of the incident photon to current efficiency is increased from 12% to 17%. Under AM 1.5 conditions, the photocurrent density reaches approximately 1.2 mA/cm(2) at 1.5 V vs. RHE and the onset potential changes to 0.8 V vs. RHE (using a Zn-Co co-catalyst).
CRIS-Team WoS Importer:2021-10-18

Magnetite-Free Sn-Doped Hematite Nanoflake Layers for Enhanced Photoelectrochemical Water Splitting - Ahn, Hyo-Jin; Kment, Stepan; Yoo, Jeong Eun; Nguyen, Nhat Truong; Naldoni, Alberto; Zboril, Radek; Schmuki, Patrik (ChemElectroChem, 2022)
In the present work, we report a preparation strategy for hematite phase-pure photoanodes consisting of Sn-doped hematite nanoflakes/hematite thin film bilayer nanostructure (Sn-HB). This approach is based on a two-step annealing process of pure iron films deposited on fluorine doped tin oxide (FTO) substrates by advanced magnetron sputtering. While the high density hematite ultrathin nanoflakes (HNs) with detrimental iron oxide layers (Fe3O4 and/or FeO) are generated during the first annealing step at 400 degrees C for two hours, the second thermal treatment at 800 degrees C for 15 minutes oxidises all the undesired iron oxide phases to a photoactive hematite layer as well as is providing efficient Sn doping of a drop-casted SnCl4 in order to increase the conductivity. The optimized Sn-HB shows an around 11 times higher photocurrent density (0.71 mA cm(-2) at 1.23 V-RHE) compared with a reference hematite photoanode produced from iron foil under the same conditions.
CRIS-Team WoS Importer:2022-06-17